The Effect of Ambon Banana (Musa acuminata Colla) Consumption on VO₂max in Futsal Athletes - Novia Zuriatun Solehah; Junendri Ardian; Muhammad Idham (Journal of Global Nutrition, 2026)
Abstract : Proper nutritional intake is a key factor in supporting optimal athletic performance during competition . Bananas are a natural source of energy that can help improve endurance due to their carbohydrates content and essential nutrients such as potassium . Potassium plays an important role in carbohydrates metabolism , including the formation and storage of glycogen and glucose as energy sources , thereby helping to maintain muscle function . This study aimed to determine the effect of Ambon banana consumption on improving VO₂ Max. Methods : This study employed a quasi-experimental method with a quantitative approach using a one-goup pretest-posttest design . A total of 37 participants were given an intervention in the form of 150 gams of whole Ambon banana daily for 7 days . Results : The results showed that the mean VO₂ Max value increased from 36,360 before the intervention to 39,570 after the intervention . Statistical analysis indicated a significant effect of Ambon banana consumption on improving VO₂ Max (p < 0.05). Conclusion : The consumption of Ambon bananas has a significant effect on Improving VO₂ Max in Futsal players .